PENERAPAN MEDIA EXE LEARNING UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR DIKELAS X SMA NEGERI 9 PEKANBARU - Annisa Mailia Ulfa; Herdini '; R. Usman Rery (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research aims to increase student learning achievement on the topic of atomic structure and periodic system of element in class X Senior High School (SMAN) 9 Pekanbaru. The research were implemented in SMAN 9 Pekanbaru started at the end of July until September 2015. Population of this research is class X5 until class X8. The research is using randomized control group pretest-posttest design. The Analysis technique used normality Liliefors to see same variance samples. After doing normality and Homogeneity test. The samples of this research were the students of class X8 as the experimental class and students of class X7 as the control class. Experimental class is a class that is applied to media eXe Learning while the control class was not. Data analysis technique used is the t-test. Based on data dk (32 +35)-2 =65 and α= 0,05 obtained ttable 1,67 and tcount 2,54. tcount > ttable is 2,54 >1.67, means that the application of media eXe Learning can improve student learning achievement on the topic of structure and periodic system of element in class X Senior High School (SMAN) 9 Pekanbaru with effect (KP) 9,03%Keywords : Achievement of Learning, eXe Learning, Atomic Structure and Periodic System of Element